Армянские либералы и конституционное движение в Османской империи: 1867-1876 гг. - Сафрастян, Рубен («Զանգակ - 97»)
The problem of relations between "Young Ottomans" — first Türk constitucionalists of 1860-1870-s and liberal movements of non-muslim peoples of Ottoman Empire has been studed insufficiently. The paper deals with the attitude of Armenian liberal circles of Ottomam Empire towards "Young Ottomans". Analysing their position reflected in publications of Armenian liberal periodicals author picks stages of its evolution out: from welldisposed interest up to direct involvement in constitutional movement. At the same time author comes to a conclusion, that existed cssential ideological differences of approach to national question and interpretation of doctrine of ottomanism stood in the way of establishing real alliance between them.
Keywords: История; Политика